Three new species of the genus Conophyma Zubovsky, 1898 (Orthoptera, Acridoidea, Catantopidae, Conophyminae) from Xinjiang, China - Zhang, Yu-Long; Xu, Qiang; Zhang, Dao-Chuan (Zootaxa, 2015)
Three new species of the genus Conophyma Zobovsky, 1898 from Xinjiang, West China are described in this paper. The Conophyma xiai sp. nov. is similar to C. olive Huang, 2006, but differs from latter by: vertical diameter of eyes 1.7 times subocular furrow, minimum width of interspace of mesosternum 1.6 times length, hind tibia yellow and furculae smaller. The new species Conophyma nigrifemora sp. nov. is similar to C. xiai sp. nov., but differs from latter by: vertex of head longer, apex narrower; posterior margin of pronotum straight; minimum width 1.6 times its length in interspace of mesosternum; posterior margin of epiproct with curve projection in the middle; epiphallus almost straight on the lower margin, The new species Conophyma hejinensis sp. nov. is similar to C. rufitibia Li & Ti, 1995, but differs from latter by: anterior and posterior margin of pronotum excised in the middle, minimum width of interspace of mesosternum 1.2 times length, hind tibia yellow and posterior margin of epiproct straight, with acute projection in the middle. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China